Bipolar H ii regions produced by cloud–cloud collisions. (17th January 2018) - Whitworth, Anthony; Lomax, Oliver; Balfour, Scott; Mège, Pierre; Zavagno, Annie; Deharveng, Lise
Abstract: We suggest that bipolar H ii regions may be the aftermath of collisions between clouds. Such a collision will produce a shock-compressed layer, and a star cluster can then condense out of the dense gas near the center of the layer. If the clouds are sufficiently massive, the star cluster is likely to contain at least one massive star, which emits ionizing radiation, and excites an H ii region, which then expands, sweeping up the surrounding neutral gas. Once most of the matter in the clouds has accreted onto the layer, expansion of the H ii region meets little resistance in directions perpendicular to the midplane of the layer, and so it expands rapidly to produce two lobes of ionized gas, one on each side of the layer. Conversely, in directions parallel to the midplane of the layer, expansion of the H ii region stalls due to the ram pressure of the gas that continues to fall towards the star cluster from the outer parts of the layer; a ring of dense neutral gas builds up around the waist of the bipolar H ii region, and may spawn a second generation of star formation. We present a dimensionless model for the flow of ionized gas in a bipolar H ii region created according to the above scenario, and predict the characteristics of the resulting free–free continuum and recombination-line emission. This dimensionless model can be scaled to the physical parameters of any particular system. Our intention is that these predictions will be useful in testing the scenario outlined above, and thereby providing indirect support for the role of cloud–cloud collisions in triggering star formation.